Os vinte anos da Lei de Libras: desafios silenciosos da inclusão em um Brasil “Barulhento” - Krutzmann, Maiquel (Universidade Federal do Tocantins, 2023)
In Brazil, according to statistical data, there are about 10 million deaf people. This significant portion of the population has seen the rise of their rights and their recognition as citizens in recent decades. There are still large gaps in the area of materializing public policies, with a view to overcoming the challenges and achieving the social inclusion of deaf people in Brazilian society as a whole, in all areas. To this end, it is necessary to celebrate the recognition of the Brazilian Sign Language (Libras) “as an objective means of communication and commonly used by deaf communities in Brazil” from Law nº 10.436/02, which guaranteed greater visibility to the deaf population. For this reason, this research aims to understand what are the advances, challenges and possible gaps in the field of social inclusion of deaf people in Brazil. Using bibliographic and documentary research as a technical procedure, the work elects the following theoretical frameworks: recognition of deaf people in Brazil based on statistical data and concepts of culture and deaf identities; legislative advances in the field of social inclusion of these people, based on the LIBRAS Law; the comparison of inclusion actions in the area of education with other equally important areas of society, such as health, leisure, commerce, public security and emergency services, for example, guiding possible gaps. In addition to the legal frameworks, the bibliographic review is essential for the foundation of the analyzes that the present work proposes to establish.